CLAIMS OF FACT IN THE ARGUMENTATION ON ISSUES OF ISLAMIC COUNTRIES IN NEWSWEEK INTERNATIONAL MAGAZINE - Rohmani Nur Indah (Universitas Muhammadiyah Surakarta, 2007)
Argumentation is basically the art of influencing others through the medium ofreasoned discourse. This research deals with how rhetorical strategies are employedin reasoned discourses especially those written in mass media read by internationalreaders. The reasoning must be based on the principles of claim presentation. Theevidences used to support the claim become significant as they portray issues inIslamic countries. Employing descriptive qualitative design, this research examinesthe writer’s opinion column and world view section in Newsweek InternationalMagazine published currently. The analysis is made on the claim, method ofdefense as well as the rhetorical strategies employed in organizing the ideas of theargument.